The criminalization of the treason against the state and the monarch in the «Rights, according to which the people of Malorossia are judged» - Колос, Михайло Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article is devoted to the results of the research of criminal law provisions of the «Rights, according to which the people of Malorossia are judged» of 1743, aimed at protecting the majestat of the Russian emperor on the Ukrainian Hetmanschyna territories in the first half of the XVIII century. The material basis of the scientific research was the legal document mentioned above, processed by scholars of V. M. Korets’kyi State and Law Institute and M. S. Hrushevskyi Institute of Ukrainian Archaeography and Source Studies of the National Academy of Sciences of Ukraine. During the research other sources of normative and legal and monographic content were used, in particular the Statute of the Grand Duchy of Lithuania in the wording of 1529, 1566, 1588, research papers of scholars and relevant reference books. Dogmatic analysis of the criminal law provisions, aimed at protecting the majestat of the monarch of the Russian Empire and his safety in the Hetmanschyna, enabled the researcher to conclude that the drafters of the «Rights, according to which the people of Malorossia are judged» stipulated the territorial principle of bringing to criminal responsibility of persons, who had committed those crimes. The author reasonably proves that the theoretical basis of components of a crime consisted of objective and subjective features typical for the current criminal law legislation. He states that the examined provisions of the mentioned act contain the ideas of the Roman criminal law and acts of the Rus’ and Lithuanian-Rus’ states. According to the author, penalties for assault on the majestat of the Russian monarch and treason against the state were formulated by the drafters of the «Rights, according to which the people of Malorossia are judged» with account of the social value of these institutions, socially dangerous character of the analyzed crimes, personality of offender and corresponded to the historical period of development of Hetmanschyna. The author considers that a positive feature of the provisions of this act, which provided a criminal legal protection of the majestat of the monarch and state security, was elimination of legal responsibility of the offender’s relatives, who did not know about his illegal behaviour, as well as encouragement of potential criminals to refuse to commit crimes and notify about their preparation to the relevant authorities.